RUSSIAN PUBLICATIONS ON EDUCATION IN THE MIRROR OF SCOPUS - Ivan E. Zadorozhnyuk; Tatyana N. Stukalova (Высшее образование в России)
The paper analyzes the specificity of the position of Russian socio-humanitarian journals in Scopus citation database, addresses the lacuna of publications on educational issues that does not correspond to the declared by Scopus principle of geographical diversification. The authors stress the need for presence in the Scopus the publications covering the perspective of domestic higher education. Researchers in many countries including European consider the investigations of Russian theorists of higher education to be worthy of attention because of their creative and look-ahead character.